1974
DOI: 10.1084/jem.140.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Activation of T and B Lymphocytes in Vitro

Abstract: The studies presented herein have focused on the biological and biochemical properties of a nonspecific mediator produced by populations of activated T lymphocytes during short-term in vitro reactions with foreign alloantigens. We have analyzed the activity of the unseparated and of chromatographically separated fractions of the supernatants from such cultures on the in vitro responses of mouse lymphocytes to soluble and macrophage-bound DNP-carrier conjugates and also to particulate heterologous erythrocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1975
1975
1979
1979

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Previous findings have indicated that the allogeneic effect factor(s) may display a limited specificity, preferentially activating B lymphocytes syngeneic to the stimulator and responder cells (13). In the past two sections we have demonstrated that the C.C3.11.75 cell only induces specific helper function with B cells sharing H-2 k subregion(s) with the strain used for stimulation.…”
Section: Specificity Of An Allogeneic Effect Factormentioning
confidence: 94%
See 1 more Smart Citation
“…Previous findings have indicated that the allogeneic effect factor(s) may display a limited specificity, preferentially activating B lymphocytes syngeneic to the stimulator and responder cells (13). In the past two sections we have demonstrated that the C.C3.11.75 cell only induces specific helper function with B cells sharing H-2 k subregion(s) with the strain used for stimulation.…”
Section: Specificity Of An Allogeneic Effect Factormentioning
confidence: 94%
“…In studying the specificity and mechanism of action, Kettman and Skarvall, measuring responses of third-party B lymphocytes (bystander), confirmed that histocompatible differences were required for triggering and demonstrated that the response could be mediated through release of soluble factors (18). Subsequent work on such factors has indicated that, depending on the in vitro system used, the factors act either nonspecifically (in terms of H-2 haplotype [19]) or exhibit a limited strain specificity (13,20).…”
Section: Specificity Of An Allogeneic Effect Factormentioning
confidence: 99%
“…These findings are most easily explained by assuming the action of a nonantigen-specific mediator (TRF) (15), which is produced by the KLH-primed T cells (7,10,13) upon the reaction with KLH and which helps the DNPBGG or DNPOVA-stimulated B cells in the production of anti-DNP antibodies. A similar effect has been described by Hartmann (17) in the primary reaction of B cells to heterologous erythrocytes in vitro, and the reconstitution of the anti-SRBC reaction of T-cell-deprived spleen cells by TRF or similar nonspecific T-cell factors is well established (4,(8)(9)(10)(11)(12)(13)(14)(15), both in the primary and in the secondary (16) in vitro responses. IfTRF should be identical with the mediator active in the system described here, it is important to demonstrate that, like TRF, it is produced by the activated T cells.…”
Section: Resultsmentioning
confidence: 51%
“…In vitro studies have shown that T-cell-replacing factor (TRF),I a nonantigen-specific mediator produced by activated T cells (15), can replace T cells in primary and secondary immune responses to heterologous erythrocytes (15,16). The action of TRF and similar factors described by other authors (4,(7)(8)(9)(10)(11)(12)(13)(14) has so far been demonstrated by restoring the immune response to heterologous erythrocytes in T-cell-deprived cultures by addition of preparations containing the factor. On the other hand, the experiments reported by Hartmann (17) have shown that T cells activated to erythrocyte antigens in vivo do, upon antigenic challenge in vitro, not only restore the response of B-cell cultures to the epitopes of the same erythrocytes, but also to those of erythrocytes from another species added simultaneously to the same cultures.…”
mentioning
confidence: 96%
See 1 more Smart Citation